CASE REPORTSImplantation of an epicardial lead through minithoracotomy as an alternative for patients with leadrelated endocarditis who require permanent pacing - Bartczak, Karol; Walczak, Andrzej; Jander, Sławomir; Zwoliński, Radosław; Banyś, Andrzej; Ammer, Arkadiusz; Wranicz, Jerzy Krzysztof; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
We present a case of a 60-year-old man who underwent mitral valve replacement, coronary artery bypass grafting and numerous electrophysiological procedures which resulted in infective endocarditis and the necessity of extracting his permanent pacemaker (PPM). In spite of multiple targeted antibiotic therapies and sustained fever, the patient had a second PPM implanted through mini-thoracotomy to provide permanent pacing.